2021
DOI: 10.3390/metabo11050305
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Lipidomic Profiling of Dry Blood Spots Using SFC-HRMS

Abstract: Lipids are essential cellular constituents that have many critical roles in physiological functions. They are notably involved in energy storage and cell signaling as second messengers, and they are major constituents of cell membranes, including lipid rafts. As a consequence, they are implicated in a large number of heterogeneous diseases, such as cancer, diabetes, neurological disorders, and inherited metabolic diseases. Due to the high structural diversity and complexity of lipid species, the presence of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The separation of oxidized lipids as well as the study of positional isomers can benefit from SFC-MS approaches due to the properties of this lipidomic approach [66]. From the eligible studies, only one study using SFC-MS matched the selection criteria and focused on method development and detection of complex lipids [37]. It allowed the identification from DBS of 500 lipid species from several classes of lipids, such as phospholipids, sphingolipids, free fatty acids, sterols, and fatty acyl-carnitines.…”
Section: Ms Lipidomic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The separation of oxidized lipids as well as the study of positional isomers can benefit from SFC-MS approaches due to the properties of this lipidomic approach [66]. From the eligible studies, only one study using SFC-MS matched the selection criteria and focused on method development and detection of complex lipids [37]. It allowed the identification from DBS of 500 lipid species from several classes of lipids, such as phospholipids, sphingolipids, free fatty acids, sterols, and fatty acyl-carnitines.…”
Section: Ms Lipidomic Approachmentioning
confidence: 99%
“…Considering the identification of DBS lipid species, different lipid classes were analysed and identified, such as FA, PUFA [20-23, 26, 29, 36, 38], or acylcarnitines [17,18], mainly analysed by GC-MS with a few studies by LC-MS. Other classes of complex lipids like sphingolipids [27,35], PL, Chol, TG, prenols, CER, and sterols [13,15,19,24,25,28,37,39] were analysed either by LC-MS, DI-MS, or SFC-MS. However, only one study solely reported the identification of several variables of the lipid fraction, not specifying lipid classes or species (Table 2) [16].…”
Section: Lipid Profile Identified From Dbs Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, normal phase chromatography and hydrophilic interaction liquid chromatography (HILIC) separate lipids in a lipid class-dependent manner, while in reversed-phase chromatography a lipid species-specific separation behavior is facilitated. Both principles are widely applied in lipidomic studies as described by Harrieder et al (2022 ), while promising methods utilizing supercritical fluid chromatography for separation are under development ( Wolrab et al, 2020 ; Le Faouder et al, 2021 ) that should enable class-wise separation of plasmanyl and plasmenyl lipid species, which in comparison with strategies refined for DI methods (necessary to correct for type-II isotopic effects) should allow high-throughput lipidomics with plasmalogen resolution on a whole lipidome scale.…”
Section: Mass Spectrometry-based Ether Lipid Analysismentioning
confidence: 99%
“…Some classes will be overlooked, while others will be enriched [ 61 ]. Depending on the goal of the study, the extraction can also be divided into “global” metabolomics [ 56 ], polar (primary) metabolomics [ 62 ], and lipidomics [ 63 ], which can be further subdivided and tailored for less abundant lipid classes, such as polyunsaturated fatty acids [ 64 ], steroids [ 65 ], or the epilipidome [ 66 ].…”
Section: Experimental Designmentioning
confidence: 99%